Unpacking ketogenic diet impact on diabetes: a systematic review - Gupta, Bhupesh; Goel, Ramita; Patel, Jaimish S.; Gupta, Kirtika; Mittal, Anshu (International Journal of Research in Medical Sciences, 2025)
This study used a literature review of various studies to examine the effects of VLC/KD on the level of glycated haemoglobin, body weight, blood sugar, lipid metabolism, and cardiovascular, renal, and neurological hazards in people with pre-diabetes or T2D. A thorough review of the literature was done with the assistance of expert librarians utilizing internet-based databases (Embase, PubMed, and the Cochrane Library). To provide a comprehensive overview of the study categories, methods, participants, the impact of the ketogenic diet on individuals with diabetes mellitus, and results, the gathered data were analyzed using descriptive statistics. According to review findings, the ketogenic diet considerably improves lipid profiles, glycaemic management, and weight loss when compared to controls. These results highlight the need to emphasise the significance of higher fibre, foods with a low glycaemic index, like legumes, vegetables and fruits, and entire grain cereals, as well as the replacement of monounsaturated fat sources for the consumption of saturated fat sources of information, in energy-balanced conditions, among individuals with diabetes.